FORMULASI KEBIJAKAN TATA RUANG RENCANA TRACE KALICILIWUNG (STUDI KASUS PELAKSANAAN PERGUB DKI JAKARTA NOMOR 163 TAHUN 2012). - Fakhrul Ramadhan (2022)
The purpose of this study is to discuss the political dynamics in the formulation of policies and programs. Formulation of Spatial Policy on Ciliwung River Spatial Plan: (Case Study of Implementation of DKI Jakarta Governor Regulation Number 163 of 2012) using Public Policy Actors Theory. The method used is descriptive qualitative. The final result of this study shows that institutions need to involve various stakeholders to determine common interests. Involvement of various actors in the formulation of the Ciliwung River Footprint Spatial Planning Policy: (Case Study on Implementation of DKI Jakarta Governor Regulation Number 163 of 2012) consisting of the DKI Jakarta Provincial Government, DPRD, academics, NGOs, stakeholders and mass media in which the DKI Jakarta Provincial Government as an institution local government. has a central role as a facilitator, coordinator based on the authority and ability to manage, implementing the Ciliwung River Trace Plan development program: (Case Study on Implementation of DKI Jakarta Governor Regulation Number 163 of 2012) which is manifested in the form of a local government work plan which is described on the Implementation of Land Acquisition for Development in the Public Interest (hereinafter referred to as Perpres No. 71/2012). In the area stratification around the river, there are 28 percent of households who reject the normalization of the Ciliwung River. Meanwhile, in the stratification that is not located around the river or areas that are not directly adjacent to the Ciliwung River, the percentage that rejects river normalization is 22 percent